Strategy of development of kazakh schools – national idea «Mangilik El» (Journal of Philosophy, Culture and Political Science, 2016)
17 January 2014 President of Kazakhstan N. A. Nazarbayev proposed to develop and adopt a Patriotic document «Mangilik El». The national idea «Mangilik El» is a kind of motivation for improvement of the education system. Since, the interest in the Kazakh language has been steadily increasing, this suggests that the Kazakh language is the language of our state, it’s the language of science and education. But unfortunately by the end of 2013/2014 academic year compared with the previous year, the total number of schools fell by 1 %. And this despite the fact that, the number of students is 1,9% more than in the previous academic year. So last year was reduced in schools the number of hours allotted to the teaching of the Kazakh language, therefore, need not be reduced, and the increase in all schools, including Kazakh, Russian and mixed schools, the number of hours devoted to studying of the Kazakh language. Аlso need to increase the level of knowledge, create favorable conditions, especially the schools of the rural population, and in General to increase the number of Kazakh schools. And the competent authorities should keep this issue constantly under control.